2021
DOI: 10.1038/s42003-021-02434-1
|View full text |Cite
|
Sign up to set email alerts
|

Cuticular hydrocarbons are associated with mating success and insecticide resistance in malaria vectors

Abstract: Anopheles coluzzii females, important malaria vectors in Africa, mate only once in their lifetime. Mating occurs in aerial swarms with a high male-to-female ratio, where traits underlying male mating success are largely unknown. Here, we investigated whether cuticular hydrocarbons (CHCs) influence mating success in natural mating swarms in Burkina Faso. As insecticides are widely used in this area for malaria control, we also determined whether CHCs affect insecticide resistance levels. We find that mated male… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 56 publications
2
22
3
Order By: Relevance
“…Elevated levels of cuticular hydrocarbons have been associated with pyrethroid resistance in An. coluzzii mosquitoes from Valle du Kou [ 10 , 54 ] in Burkina Faso and evidence of an association between epicuticle thickness and insecticide resistance has been reported in several additional Anopheles populations [ 11 , 55 ]. As this resistance mechanism may confer cross resistance to a wide range of contact insecticides, it is important that insecticide screening pipelines incorporate strains with thickened cuticles.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Elevated levels of cuticular hydrocarbons have been associated with pyrethroid resistance in An. coluzzii mosquitoes from Valle du Kou [ 10 , 54 ] in Burkina Faso and evidence of an association between epicuticle thickness and insecticide resistance has been reported in several additional Anopheles populations [ 11 , 55 ]. As this resistance mechanism may confer cross resistance to a wide range of contact insecticides, it is important that insecticide screening pipelines incorporate strains with thickened cuticles.…”
Section: Discussionmentioning
confidence: 99%
“…As this resistance mechanism may confer cross resistance to a wide range of contact insecticides, it is important that insecticide screening pipelines incorporate strains with thickened cuticles. However, our own observations indicate that this mechanism may be less stable in laboratory colonies than other resistance mechanisms, perhaps indicative of a high fitness cost which is balanced by other phenotypic advantages, such as ability to withstand desiccation [ 56 ], or mating advantage [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The An. coluzzii mosquitoes endemic to this part of Burkina Faso – hereafter named AcVK5 – are highly resistant to pyrethroids (9, 11, 26). AcVK5 mosquitoes were exposed to ATQ for 6 minutes (min) at two concentrations (100 µmol- or 1 mmol/m 2 ) or a mock-treated blank control surface prior to feeding on infectious blood samples.…”
Section: Resultsmentioning
confidence: 99%
“…Cuticular hydrocarbons of the mosquito egg have been listed as oviposition pheromones for Ae. aegypti [ 32 ]. We found that OR38, OR93, OR110, OR112, OR115-V2 and OR115-V3 genes were highly expressed before oviposition and that their expression decreases after oviposition, suggesting that they may play a role in mosquito oviposition in combination with oviposition stimulants.…”
Section: Discussionmentioning
confidence: 99%